Global changes in bladder cancer mortality in the elderly. (February 2023) - Tempo, Jake; Yiu, Ting Wai; Ischia, Joseph; Bolton, Damien; O'Callaghan, Michael
Abstract: Background: Bladder cancer is the 14th most common cause of cancer deaths worldwide and has a mean age of diagnosis of 73 years. Elderly people have fewer curative treatment options for muscle invasive bladder cancer. The aim of this study is to investigate how bladder cancer mortality has changed over the past forty years in different world regions to assess discrepancies between elderly and younger patients with bladder cancer. Methods: Bladder cancer mortality data were extracted from the World Health Organisation's GLOBOCAN database. Age-standardised mortality rates (ASMR) for bladder cancer were computed by year, sex, region and Human Development Index (HDI) using the world standard population. Results: Overall ASMR in all available countries with data between 1986 and 2014 for men aged ≥ 75 has decreased from 101.2 to 89.9 per 100, 000 (−11.2%). The decrease in ASMR for men < 75 has been 0.3–2.0 per 100, 000 (−39.4%). In women aged ≥ 75 ASMR has decreased from 26.9 to 22.5 per 100, 000 (−16.4%) and in women < 75 the ASMR has decreased from 0.76 to 0.56 per 100, 000 (−26.4%). Correlation analysis showed a positive linear relationship between Human Development Index (HDI) and improvement in age-standardised mortality rate in all ages. Pearson's coefficient showed that correlation was strongest in the 60–74 age group (r = −0.61, p < 0.001) and weakest in those aged ≥ 75 (r = −0.39, p = 0.01). Conclusion: Bladder cancer mortality is not improving in the elderly at the same rate as the rest of the population. Particular focus should be applied in future research to enhance and expand treatment options for bladder cancer that are appropriate for elderly patients. Highlights: Global age-standardised mortality between 1986 and 2014 for bladder cancer has decreased by 11% in men ≥ 75 compared to 39% in men < 75. Global age-standardised mortality between 1986 and 2014 for bladder cancer has decreased by 16% in women ≥ 75 compared to 26% in women < 75. There is a positive linear relationship between a country's Human Development Index and age-standardised mortality rate in all age groups with the correlation weakest in those aged ≥ 75.